THE SETTING ANALYSIS IN DEREK KOLSTAD’S JOHN WICK - Praditya, Wisma Agung; Suarniti, Gusti Ayu Made Rai; Kertiasih, Ni Nyoman (Ma Chung Press, 2023)
This paper analyzes the distinctive settings in Derek Kolstad's John Wick movie, emphasizing its unique portrayal of the Continental Hotel in the USA and its reflection of contemporary American society. Using qualitative research methods, the study examines both primary data from the movie script and secondary data from relevant sources. The findings highlight the film's use of physical, time, and social environment settings. The physical setting unfolds in a fictional, gritty version of urban settings, primarily New York City. Time setting is conveyed through markers like continuous action, character development, and visual cues. The social environment setting explores family dynamics, social institutions, and the presence of law enforcement. The analysis concludes by summarizing the film's use of setting to create atmosphere, act as a dominant element, and contribute to the overall narrative, enhancing our understanding of its acclaimed intense action sequences and exploration of a life immersed in violence.